2017
DOI: 10.1016/j.jamcollsurg.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of a Surgical Consensus Guideline in Breast-Conserving Surgery

Abstract: Background The SSO/ASTRO consensus statement was the first professional guideline in breast oncology to declare “no ink on tumor” as a negative margin in patients with stages I/II breast cancer undergoing breast conservation therapy (BCT). We sought to analyze the financial impact of this guideline at our institution using a historic cohort. Study Design We identified women undergoing re-excision following breast-conserving surgery for invasive breast cancer from 2010–2013 using a prospectively-maintained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In this era of multidisciplinary therapy, “no ink on tumor” is now becoming a standard policy to grasp the appropriateness of the margins in surgery operations. In fact, it is associated with low rates of ipsilateral true breast tumor recurrence and has the potential to decrease re-excision rates, improve cosmetic outcomes and decrease health care cost 13,14…”
Section: Introductionmentioning
confidence: 99%
“…In this era of multidisciplinary therapy, “no ink on tumor” is now becoming a standard policy to grasp the appropriateness of the margins in surgery operations. In fact, it is associated with low rates of ipsilateral true breast tumor recurrence and has the potential to decrease re-excision rates, improve cosmetic outcomes and decrease health care cost 13,14…”
Section: Introductionmentioning
confidence: 99%
“…Only direct medical costs were reported; indirect costs (not directly accountable to the operation) and intangible costs (unquantifiable cost relating to an identifiable source) were not estimated in any of the reviewed literature. The source of cost estimates was hospital records in four studies and Centers for Medicare and Medicaid Services reimbursement data in three. Initial BCS and reoperation costs were in the range US $1234–11786 and $655–9136 respectively ( Table S2, supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…The present health economic review highlights the heterogeneity and paucity of high‐quality studies reporting cost estimates of reoperations in breast surgery. Only nine studies have commented on reported costs of re‐excision in BCS, with two employing a predictive model to hypothesize the cost impact of re‐excision following BCS in the USA and Canada. Several studies contained minimal cost information, whereas others reported a range of costs for numerous variables that could not be collated accurately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Numerous studies have also suggested a negative financial and social impact associated with the need for re-excision. 2 Most surgeons agree that achieving negative margins at the initial surgery can significantly improve cosmetic outcome as well. As frozen sections are impractical because of both the need for additional operating room times (up to 30 minutes) and variable accuracy and physical availability of staff and/or equipment for routine partial mastectomy, various modalities have been developed to reduce the risk of a positive margin.…”
Section: The Influence Of Breast Density On the Utility Of Marginprobe In Partial Mastectomymentioning
confidence: 99%